Safety and Efficacy of Intracoronary Infusion of Allogeneic Human Cardiac Stem Cells in Patients With ST-Segment Elevation Myocardial Infarction and Left Ventricular Dysfunction: A Multicenter Randomized, Double-Blind, and Placebo-Controlled Clinical Trial. Issue 5 (17th August 2018) - Fernández-Avilés, Francisco; Sanz-Ruiz, Ricardo; Bogaert, Jan; Casado Plasencia, Ana; Gilaberte, Inmaculada; Belmans, Ann; Fernández-Santos, Maria Eugenia; Charron, Dominique; Mulet, Miguel; Yotti, Raquel; Palacios, Itziar; Luque, Manuel; et al.
Abstract : Rationale: : Allogeneic cardiac stem cells (AlloCSC-01) have shown protective, immunoregulatory, and regenerative properties with a robust safety profile in large animal models of heart disease. Objective: : To investigate the safety and feasibility of early administration of AlloCSC-01 in patients with ST-segment–elevation myocardial infarction. Methods and Results: : CAREMI (Safety and Efficacy of Intracoronary Infusion of Allogeneic Human Cardiac Stem Cells in Patients With STEMI and Left Ventricular Dysfunction) was a phase I/II multicenter, randomized, double-blind, placebo-controlled trial in patients with ST-segment–elevation myocardial infarction, left ventricular ejection fraction ⩽45%, and infarct size ≥25% of left ventricular mass by cardiac magnetic resonance, who were randomized (2:1) to receive AlloCSC-01 or placebo through the intracoronary route at days 5 to 7. The primary end point was safety and included all-cause death and major adverse cardiac events at 30 days (all-cause death, reinfarction, hospitalization because of heart failure, sustained ventricular tachycardia, ventricular fibrillation, and stroke). Secondary safety end points included major adverse cardiac events at 6 and 12 months, adverse events, and immunologic surveillance. Secondary exploratory efficacy end points were changes in infarct size (percentage of left ventricular mass) and indices of ventricular remodeling by magnetic resonance at 12 months. Forty-nine patients were included (92% male, 55±11 years), 33 randomized to AlloCSC-01 and 16 to placebo. No deaths or major adverse cardiac events were reported at 12 months. One severe adverse events in each group was considered possibly related to study treatment (allergic dermatitis and rash). AlloCSC-01 elicited low levels of donor-specific antibodies in 2 patients. No immune-related adverse events were found, and no differences between groups were observed in magnetic resonance–based efficacy parameters at 12 months. The estimated treatment effect of AlloCSC-01 on the absolute change from baseline in infarct size was −2.3% (95% confidence interval, −6.5% to 1.9%). Conclusions: : AlloCSC-01 can be safely administered in ST-segment–elevation myocardial infarction patients with left ventricular dysfunction early after revascularization. Low immunogenicity and absence of immune-mediated events will facilitate adequately powered studies to demonstrate their clinical efficacy in this setting. Clinical Trial Registration: : URL:http://www.clinicaltrials.gov . Unique identifier: NCT02439398. Abstract : Supplemental Digital Content is available in the text.